Analisis Perilaku Perawat terhadap Implementasi Hand Hygiene dalam Pencegahan Kejadian Infeksi Nosokomial di Ruang Rawat Inap RS TK IV IM 07.01 Kota Lhokseumawe - Abrar, Abrar; Asriwati, Asriwati; Yuniati, Yuniati (Jurnal Ners, 2024)
Nurses as professional staff in hospitals cannot avoid the risk of microbial contamination. Therefore, hand hygiene is crucial for nurses. The main cause of nosocomial infections in healthcare facilities is proper hand hygiene practices. In Indonesia, the nosocomial infection rate in hospitals reaches 15.74 percent, and globally, good hand hygiene can reduce nosocomial infection incidents by up to 30 percent. This study aims to analyze nurses' behavior regarding hand hygiene implementation in the initiative to prevent nosocomial infections in the inpatient ward of RS TK IV IM 07.01 Lhokseumawe. This research uses a quantitative method with a Cross-Sectional design. The study was conducted in the Inpatient Ward of RS TK IV IM 07.01 Lhokseumawe. The study population consists of all nurses working in the inpatient ward, totaling 65 people. The sampling technique involved the entire population, namely 65 respondents. Data collection was carried out through questionnaire completion. The collected data were then analyzed using SPSS with univariate, bivariate, and multivariate analyses. The research results show that 56 respondents (86.15 percent) correctly perform hand hygiene, while 9 respondents (13.85 percent) do not. The chi-square statistical test revealed that knowledge, attitude, and practice have a significant relationship with hand hygiene implementation with a p-value < 0.05. The results of the multiple logistic regression test show that practice with a sig value of 0.001 and Exp(B) 11.960. The conclusion of this study is that practice is the most dominant variable associated with nurses' hand hygiene implementation. Nurses are advised to always pay attention to hand hygiene in every medical activity to prevent nosocomial infections in hospitals.